Pojęcie przedsiębiorstwa i zorganizowanej części przedsiębiorstwa na gruncie prawa podatkowego - Ilski, Michał (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2014)
The purpose of this study was a presentation of the concept of an enterprise and the concept of an organized part of an enterprise in Polish tax legislation. The study focused on The Personal Income Tax Act, The Corporate Income Tax Act, The Goods and Services Tax Act and The Tax on Civil Law Transactions Act. An interpretation of the aforementioned concepts in the jurisdiction of Polish courts was also presented. Furthermore, another aim was to look at the concept of an enterprise and the concept of an organized part of an enterprise from the point of view of European Union law. The study also tried to answer the question of whether The Goods and Services Tax Act and The Tax on Civil Law Transactions Act are compatible with European Union law